Effect of type of road humps on vehicular speeds on residential roads - Suryo Putranto Leksmono; Kurniawan Kevin (MATEC Web of Conferences, 2018)
To reduce potential pedestrian fatalities, in residential road maximum speed is 30km/hour. Apart from installing maximum speed signs, installing road humps may ensure speed reduction. This paper is intended to compare light vehicles and motorcycles speeds and speeds reductions due to road humps. Data collection was done in Modernland, Tanggerang City. Two road segments were observed, i.e. segments with standard and non-standard road humps. Observation was made in morning, noon and afternoon periods. A portable speed gun was used to measure the speed at about 50m and 25m before the road humps. Some mean difference statistical analyses were conducted for both speeds and speeds differences between different type of road humps and between pairs of observation periods. The 0.05 significant level was used. Surprisingly, mean of speeds differences (50m vs 25m) in standard road hump is significantly higher than in non-standard road hump.